تقويم تدريبات كتاب "العربية بين يديك" على ضوء تصنيف بلوم للمعرفة - Nidayatur Rohmah; M. Afif Amrulloh (LISANIA: Journal of Arabic Education and Literature, 2018)
The purpose of this study is to find out how the application the cognitive domain of Bloom taxonomy on the problems in the kitab al-'arabiyah baina yadaika. This is a descriptive research using qualitative and quantitive approach and content analysis. The researcher uses document analysis as the data collection technique. The results show that: The exercises of al-'arabiyah baina yadaika  is on the level of remembering until creating. And the exercises on the first three levels are more dominant with the precentage 85.5%. The percentage of exercises on each cognitive level in al-'arabiyah baina yadaika, when it is compared with the proportion of the basic competencies achievement analysis, the results have not met the standards.